2022
DOI: 10.1111/ijfs.15580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potato starch on the characteristics, microstructures and quality attributes of indica rice flour and instant rice noodles

Abstract: Summary The effects of partial replacement (0%–20%, w/w) of rice flour by potato starch (PS) on the physicochemical properties, microstructures, texture and in vitro digestibility of indica rice flour (IRF) and instant rice noodles (IRN) were systematically investigated. Accordingly, the addition of PS significantly increased the peak viscosity (2876.00–3221.00 mPa·s) and tan δ values (0.14–0.22) but lowered the setback values (2169.00–1036.50 mPa) of the pastes. Rice noodles with 5%–15% PS (PS and IRF at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It was observed that formulations 6, 7 and 8 with high percentages of starch showed higher expansion index (Table 3), but with a significant difference between them (p < 0.05), due to higher fat content. This behavior could be attributed to the fact that the lower the fat content, the higher the expansion rate (Saeleaw and Schleining, 2010;Cueto et al, 2015;Tiga et al, 2021;Chen et al, 2022). However, in formulations 4 and 8 showed high expansion indexes (17.24 ± 1.29 and 35.40 ± 2.90, respectively), the same behavior was observed, but it could also be explained from the point of view of the synergistic interaction between the crude fat and starch content in the formulation, which shows that there is a close dependence in the relationship between these two components that affect the increase or decrease in the expansion index, showing a trend depending on this relationship.…”
Section: Physical Characterizationmentioning
confidence: 99%
“…It was observed that formulations 6, 7 and 8 with high percentages of starch showed higher expansion index (Table 3), but with a significant difference between them (p < 0.05), due to higher fat content. This behavior could be attributed to the fact that the lower the fat content, the higher the expansion rate (Saeleaw and Schleining, 2010;Cueto et al, 2015;Tiga et al, 2021;Chen et al, 2022). However, in formulations 4 and 8 showed high expansion indexes (17.24 ± 1.29 and 35.40 ± 2.90, respectively), the same behavior was observed, but it could also be explained from the point of view of the synergistic interaction between the crude fat and starch content in the formulation, which shows that there is a close dependence in the relationship between these two components that affect the increase or decrease in the expansion index, showing a trend depending on this relationship.…”
Section: Physical Characterizationmentioning
confidence: 99%
“…The quality properties of rice noodles are mainly dependent on the textural characteristics of rice flour [5]. However, rice noodles made from native indica rice are less resistant to shear force and exhibit lower tensile strength and extensibility; thus, native indica rice cannot usually meet the requirements for processing [6][7][8]. To obtain high-quality rice noodles, food additives are commonly used, such as modified starches, hydrocolloids, emulsifiers, proteins, and enzymes [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%